(3-x)/-4=(x+6)/3

I have tried this one multiple times but i still can't get it.

2 answers

(3-x)/-4 = (x+6)/3

subtract the terms on the right over to the left (everything)

[(3-x)/-4]-[(x+6)/3]=0

find a common denominator
for 4 and 3 which is 12

[-3(3-x)/12]-[4(x+6)/12]=0

multiply over

(-9+3x)/12 - (4x+24)/12= 0

[(-9+3x)-(4x+24)]/12 = 0 don't forget the negative

(-3+3x-4x-24)/ 12 = 0

combine like terms on the numerator then solve for x

(-3+3x-4x-24)= 0
Typo after multiply over: Correction
is it's -9 not negative -3

[(-9+3x)-(4x+24)]/12 = 0 don't forget the negative

(-9+3x-4x-24)/ 12 = 0

combine like terms on the numerator then solve for x

(-9+3x-4x-24)= 0